Multiple Myeloma with scleroderma and second malignancy: A case report - Zahra Mozaheb (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2017)
Living long term with multiple myeloma recently seems to increase the long term sequel such as second primary malignancy. Several studies on second malignancy in multiple myeloma have been suggested that therapy related factors and predisposing host factor also are responsible. Scleroderma is reported with solid tumors in several studies, but association with multiple myeloma has seldom been reported. In this report we present a patient with multiple myeloma, scleroderma and second primary malignancy.